Within-population variation in prevalence and lineage distribution of avian malaria in blue tits, Cyanistes caeruleus. - Wood, M; Cosgrove, C; Wilkin, T; Knowles, S; Day, K; Sheldon, B (2007)
The development of molecular genetic screening techniques for avian blood parasites has revealed many novel aspects of their ecology, including greatly elevated diversity and complex host-parasite relationships. Many previous studies of malaria in birds have treated single study populations as spatially homogeneous with respect to the likelihood of transmission of malaria to hosts, and we have very little idea whether any spatial heterogeneity influences different malaria lineages similarly. Here, we report an analysis of variation in the prevalence and cytochrome b lineage distribution of avian malaria infection with respect to environmental and host factors, and their interactions, in a single blue tit (Cyanistes caeruleus) population. Of 11 Plasmodium and Haemoproteus cytochrome b lineages found in 997 breeding individuals, the three most numerous (pSGS1, pTURDUS1 and pBT7) were considered separately, in addition to analyses of all avian malaria lineages pooled. Our analyses revealed marked spatial differences in the prevalence and distribution of these lineages, with local prevalence of malaria within the population ranging from over 60% to less than 10%. In addition, we found several more complex patterns of prevalence with respect to local landscape features, host state, parasite genotype, and their interactions. We discuss the implications of such heterogeneity in parasite infection at a local scale for the study of the ecology and evolution of infectious diseases in natural populations. The increased resolution afforded by the combination of molecular genetic and geographical information systems (GIS) tools has the potential to provide many insights into the epidemiology, evolution and ecology of these parasites in the future.